Lixiviación del manganeso presente en las pilas alcalinas con ácido fórmico a distintos niveles de ph y tiempos de agitación - Carhuanira Aspiros, Marino Oswaldo (2018)
In the present work the manganese recovery present in spent alkaline batteries was studied through a leaching process using Formic Acid. Tests were carried out taking into account the concentration of HCOOH, the MP / [HCOOH] ratio maintaining first the mass of constant Raw Material (RM), and then the constant acid concentration. For the determination of the amount of Manganese recovered, the standardized method "Photometric determination of total Mn with formaldoxime was used." The concentration of HCOOH plays a very important role in the recovery of Manganese, as well as the viscosity of the HCOOH-H2O solution. The conditions to extract the highest concentration of Mn are: [HCOOH] : 2.95% Raw Material : 5 grams of pile powder Time : 8 hours Temperature : 25 ° C pH : 2.51